Best practice in communications training for public engagement with science, technology, engineering and mathematics - Karen Bultitude; Joana Silva (JCOM: Journal of Science Communication, 2009)
Effective training in key communications skills is critical for successful public engagement. However, what are the secrets to designing and delivering an effectual training course? This paper outlines key findings from a research study into communication training programmes for public engagement with STEM (science, technology, engineering and mathematics). The research focused on training in direct communication methods, (as separate from media training) and encompassed both trainers and trainees, the latter group spanning across both scientists and explainers. The findings indicated that training courses are effective at increasing involvement in science communication events and trainees feel more confident and able to engage due to training. An interactive style was found to be a key element of training courses. Demonstrations of good practice followed by own performance with feedback were also important, preferably involving a ‘real’ audience. A list of guidelines on best practice has been developed which offers practical advice.